Enhanced Stability and Highly Bright Electroluminescence of AgInZnS/CdS/ZnS Quantum Dots through Complete Isolation of Core and Shell via a CdS Interlayer - Kwon, Hyo Geun; Lee, Taesoo; Kim, Kihyo; Kim, Do Hyun; Seo, Haewoon; Kwon, O. Pil; Kwak, Jeonghun; Kim, Sang Wook (Small, 2024)
An approach for synthesizing AgInZnS/CdS/ZnS core–shell–shell quantum dots (QDs) that demonstrate exceptional stability and electroluminescence (EL) performance is introduced. This approach involves incorporating a cadmium sulfide (CdS) interlayer between an AgInZnS (AIZS) core and a zinc sulfide (ZnS) shell to prevent the diffusion of Zn ions into the AIZS core and the cation exchange at the core–shell interface. Consequently, a uniform and thick ZnS shell, with a thickness of 2.9 nm, is formed, which significantly enhances the stability and increases the photoluminescence quantum yield (87.5%) of the QDs. The potential for AIZS/CdS/ZnS QDs in electroluminescent devices is evaluated, and an external quantum efficiency of 9.6% in the 645 nm is achieved. These findings highlight the importance of uniform and thick ZnS shells in improving the stability and EL performance of QDs.
Keywords: AgInS2 quantum dot; Cadmium sulphide interlayer; Cation exchanges; Core-shell interface; Core-shell-shell quantum dots; Enhanced stability; Improved stability and electroluminescence; Performance; Zinc sulphide shell; Zn ions; AgInS2 quantum dots; CdS interlayers; improved stability and electroluminescence; ZnS shells